Mediators of slow synaptic potentials in the myenteric plexus of the guinea-pig ileum - Johnson, S. M. (1981)
1. Intracellular recordings were made from neurones in the myenteric plexus of the ileum isolated from adult guinea-pigs. 2. Three synaptic potentials were evoked in different myenteric neurones by focal stimulation of the ganglion surface at a distance of up to 100 μm from the cell body from which the recording was made. These were the fast cholinergic excitatory post-synaptic potential (e.p.s.p.), the slow e.p.s.p. and the slow inhibitory post-synaptic potential (i.p.s.p.). 3. 5-hydroxytryptamine and substance P were applied to the neurones by superfusion (10 nm-1 μm) or by electrophoresis within 5 μm of the neurone cell body. 5-HT depolarized, hyperpolarized or had no effect on approximately equal numbers of neurones, whereas substance P depolarized 90% of neurones. 4. Many neurones with a depolarizing slow e.p.s.p. were hyperpolarized by superfusion or electrophoretic application of 5-HT. 5. Superfusion with 5-HT reversibly depressed the fast e.p.s.p., slow e.p.s.p. and slow i.p.s.p. Superfusion with substance P depressed the slow e.p.s.p. 6. Methysergide (10-30 μm) reduced the amplitude of the fast e.p.s.p., the slow e.p.s.p. and the slow i.p.s.p. 7. Chymotrypsin (200 μg/ml.) reversibly reduced the amplitude of the slow e.p.s.p., but had no effect on membrane potential, the action potential or the fast e.p.s.p. Chymotrypsin reduced or abolished the depolarization caused by electrophoretic application of substance P, but had no effect on the depolarization or hyperpolarization caused by 5HT. 8. The results provide evidence that 5-HT is not the transmitter which mediates the slow e.p.s.p. in myenteric neurones. The slow e.p.s.p. may be caused by substance P or another similar peptide.